ANALISIS PERSEDIAAN LANTING DENGAN METODE ECONOMIC ORDER QUANTITY PADA TIEN SNACK DAN MEKAR ASIH KUWARASAN - Suwandi, Eko Darmawan (P4M STIE Putra Bangsa, 2016)
Supplies a wealth of companies that have an important role in business operations, so the company need to make proactive management, which means that the company must be able to anticipate the circumstance and challenges of inventory management in order to achieve the ultimate objective, which is to minimize the total cost to be incurred by the company for inventory handling. The purpose of study this was to determine the number of orders and inventory costs lanting in Tien Snack and Mekar Asih method Economic Order Quantity (EOQ). This study was conducted with data collection through observation. The result showed the number of inventory lanting Tien Snack been effective in meeting consumer demand for the company does not run out of raw material inventory and total inventory cost by using Economic Order Quantity (EOQ) is smaller than the method used by the company, but the result of research on Mekar Asih shows how much less effective whwn using Economic Order Quantity (EOQ) for the cost of supllies tend to be more expensive than existing methods existing companies. This is because Mekar Asih determine ordering cost with constan number for each message. Keyword: Inventory, EOQ.